2018
DOI: 10.1007/s10597-018-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Focus Group in Community Mental Health Research: Need for Adaption

Abstract: The article presents an analysis of the use of focus groups in researching community mental health users, starting with the reasons for using them, their implementation in mental health service users' research, and the adaptations of focus group use when researching the experiences of users. Based on personal research experience and a review of scientific publications in the Google Scholar, Web of Science, ProQuest, EBSCOhost, and Scopus databases, 20 articles published between 2010 and 2016 were selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
11
0
2
Order By: Relevance
“…It requires individuals to undergo both cognitive and behavioral adaptation . In addition, adaptation is considered to be an important feature of human health and social support and is known as a critical social health determinant . It has been reported by multiple studies that adaptation is essential for maintaining health and well‐being and achieving satisfaction and happiness …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It requires individuals to undergo both cognitive and behavioral adaptation . In addition, adaptation is considered to be an important feature of human health and social support and is known as a critical social health determinant . It has been reported by multiple studies that adaptation is essential for maintaining health and well‐being and achieving satisfaction and happiness …”
Section: Introductionmentioning
confidence: 99%
“…determinant. 23,24 It has been reported by multiple studies that adaptation is essential for maintaining health and well-being 23,24 and achieving satisfaction and happiness. 25 Social support refers to the sum of various supportive forces or factors in the social network and can greatly improve an individual's adaptation in a social context.…”
mentioning
confidence: 99%
“… 27 Focus groups have been widely used in mental health research. 28 We classified study participants into four categories: people living with MCI, family informal caregivers, GPs and community health centre (CHC) managers. Each focus group session comprised participants from the same category in order to avoid dominance of any participant category in the discussions and to maximise engagement of each participant.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported similar approaches to group‐based research contribution, where participants are able to ‘come and go’ (Zupančič et al . 2019; p. 174). The justification for this flexibility is autonomy (Polit & Beck 2017) and the quest for a sufficient quantity of data.…”
Section: Methodsmentioning
confidence: 99%